Citrin: a novel food allergen in citrus seeds and citrus-derived pectin that shows cross-reactivity with cashew and pistachio - Konstantinou, George N.; Baker, Mary Grace; Yu, Joyce; Ford, Lara S.; Bencharitiwong, Ramon; Grishina, Galina; Sampson, Hugh A.; Sicherer, Scott; Nowak-Wegrzyn, Anna (Annals of allergy, asthma, & immunology, 2023)
Patients exquisitely sensitive to cashew/pistachio are at risk for allergic reactions to citrus seeds and pectin. In this study, we sought to evaluate whether pectin is contaminated with citrus seeds, to identify a culprit antigen in citrus seeds, and to assess for cross-reactivity among allergens in citrus seeds, citrus pectin, and cashew or pistachio. Proteins from orange seed coats, orange seed endosperms, lemon seeds, grapefruit seeds, citrus pectin, apple pectin, and grapefruit pectin were extracted. Protein concentrations in all extracts were determined and visualized using sodium dodecyl sulfate–polyacrylamide gel electrophoresis technique. Immunoglobulin E-binding capacity was determined with Western blot analyses and tandem mass spectrometry for the identification of the culprit allergen in citrus seeds and pectin. In subjects with citrus seed, pectin, and cashew allergies, there was strong immunoglobulin E-reactivity to bands between 17 to 28 kDa and 28 to 38 kDa. The tandem mass spectrometry analysis of these bands indicated the presence of citrin as the culprit allergen. Citrin and Ana o 2 are both 11S globulins belonging to the cupin superfamily, and significant homology was found between these proteins. Citrus pectin may be contaminated with citrus seeds. Citrin, a newly identified allergen in citrus seeds, seems to be the culprit antigen in citrus seeds and contaminated citrus pectin. Citrin is highly homologous with Ana o 2 in cashew and Pis v 2 in pistachio, suggesting potential for cross-reactivity and providing an explanation for co-allergenicity of cashew or pistachio, citrus seeds, and citrus pectin.